Bralna pismenost slovenskih učencev v PISI 2009 - analiza skozi prizmo razvitosti kompetence "učenja učenja" - Pečjak, Sonja (Šolsko polje, 2011)
In this article, we explored the Slovenian students' achievement in reading literacy from the international study PISA 2009. We analyzed the connections between reading literacy achievement and elements of competency "learning to learn". There are two basic elements of competency "learning to learn" which are developed through self-regulated learning: regulation of cognition (knowledge of and using learning strategies) and regulation of motivation and emotion. Further on, we make parallels with the terminology used by PISA 2009 researchers: instead of regulation of motivation, they use the term "reading involvement" and instead of regulation of cognition, they use "learning/reading approaches". This is followed by a short presentation of the reading involvement concept (which is manifested as reading interest on the behavioural level) and the concept of reading approaches through the presentation of cognitive and metacognitive strategies. The PISA 2009 researchers collected data on both concepts and compared them to the level of students' reading literacy. The results of 7764 Slovenian students show that reading interest, manifested through everyday reading for pleasure is significantly higher in girls than in boys. Moreover, the latter is significantly and positively related with reading literacy. Th e same trend is found in students from OECD countries. It turned out that for reading approach, the strongest predictors of reading literacy of Slovenian students are knowing the strategies of comprehension, summarizing and using regulation strategies - planning, monitoring and evaluating one's own reading process.
Keywords: vzgoja in izobraževanje; reading literacy; bralna pismenost; branje; competence "learn to learn"; bralnost; education; reading approach; pedagoška psihologija; PISA 2009; reading engagement; raziskave; reading; literacy; learning to learn; competences; educational psychology